2020
DOI: 10.1111/dom.14109
|View full text |Cite
|
Sign up to set email alerts
|

Lower risk of severe hypoglycaemia with insulin glargine 300 U/mL versus glargine 100 U/mL in participants with type 1 diabetes: A meta‐analysis of 6‐month phase 3 clinical trials

Abstract: Severe hypoglycaemia (SH) remains a challenge to people with type 1 diabetes (T1DM), and new‐generation basal insulins may improve patient outcomes. This post hoc meta‐analysis explored the risk of SH with insulin glargine 300 U/mL (Gla‐300) versus glargine 100 U/mL (Gla‐100) in a pooled population with T1DM from three randomized, multicentre, 6‐month similarly designed phase 3 trials: EDITION 4, EDITION JP 1 and EDITION JUNIOR. Endpoints included incidence and time to first occurrence of SH. Among 629 and 626… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 16 publications
(45 reference statements)
3
24
0
1
Order By: Relevance
“…As for safety the reduction in the proportions of patients with at least one hypoglycemic event and in the incidence rates of hypoglycemia (BG B 70 mg/dl and \ 54 mg/dl) during 6 months in both groups documents that the switch from 1BI to a 2BI is safe. A recent meta-analysis in T1D demonstrated similar glycemic control with lower risk of severe hypoglycemia of Gla-300 versus Gla-100, particularly during the titration period [37].…”
Section: Discussionmentioning
confidence: 97%
“…As for safety the reduction in the proportions of patients with at least one hypoglycemic event and in the incidence rates of hypoglycemia (BG B 70 mg/dl and \ 54 mg/dl) during 6 months in both groups documents that the switch from 1BI to a 2BI is safe. A recent meta-analysis in T1D demonstrated similar glycemic control with lower risk of severe hypoglycemia of Gla-300 versus Gla-100, particularly during the titration period [37].…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, these findings indicate that although a minimal increase occurred in the insulin dosages of the patients, a reduction occurred in the frequency of hypoglycaemia. Previous randomized open-label studies reported that although switching to IGlar U300 led to a significant reduction in the frequency of hypoglycaemia, it provided suboptimal blood glucose control [11,12]. In the Edition 4 study, which included 274 patients randomized to Gla-300 and 275 to Gla-100, and a patient follow-up of 6 months, the change in HbA 1c was equivalent in the 2 treatment groups (difference 0.04%, 95% CI: -0.10 to 0.19) (0.4 mmol/mol, -1.1 to 2.1), Percentage and Gla-300 was thus deemed noninferior.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IGlar U300 provides more steady-state pharmacokinetics (PK) and pharmacodynamics (PD) profiles and a longer duration of action than IGlar U100, extending blood glucose control well beyond 24 h [ 10 ]. On the other hand, IGlar U300 has been shown to be as effective for glycaemic control as IGlar U100 in patients with long-term T1DM and to have a lower risk of hypoglycaemia and weight gain than IGlar U100 [ 11 , 12 ]. In a retrospective trial (SPARTA), IGlar U300 reduced the incidence of hypoglycaemic events while providing better blood glucose control [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk of hypoglycaemia with insulin degludec versus insulin glargine U300 in insulin-treated patients with type 2 diabetes: the randomised, head-to-head CONCLUDE trial Philis-Tsimikas A 1 , Klonoff DC 2 , Khunti K 3 , Bajaj HS 4 , Leiter LA 5 , Hansen MV 6 , Troelsen LN 6 , Ladelund S 6 , Heller S 7 , Pieber TR 8 , on behalf of the CONCLUDE Study Group 1 Scripps Whittier Diabetes Institute, San Diego, CA; 2 Diabetes Research Institute, Mills-Peninsula Medical Center, San Mateo, CA; 3 Diabetes Research Centre, University of Leicester, Leicester, UK; 4 LMC Diabetes and Endocrinology, Brampton, ON, Canada; 5 Li Ka Shing Knowledge Institute, Division of Endocrinology & Metabolism, St Michael's Hospital, University of Toronto, ON, Canada; 6 Novo Nordisk A/S, Søborg, Denmark; 7 Academic Unit of Diabetes, Endocrinology and Metabolism, University of Sheffield, Sheffield, UK; 8 Division of Endocrinology and Diabetology, Department of Internal Medicine, Medical University of Graz, Graz, Austria Diabetologia 2020; 63: 698-710…”
Section: Utlra-long-acting Insulin Analogs: Head-to-head and Real-world Observational Comparisons Between Insulin Glargine U300 And Insulmentioning
confidence: 99%